A System Calibration and Fast Iterative Reconstruction Method for Next-Generation SPECT Imagers - Miller, Brian W. (IEEE Trans Nucl Sci, 2012)
Recently, high-resolution gamma cameras have been developed with detectors containing > 10(5)–10(6) elements. Single-photon emission computed tomography (SPECT) imagers based on these detectors usually also have a large number of voxel bins and therefore face memory storage issues for the system matrix when performing fast tomographic reconstructions using iterative algorithms. To address these issues, we have developed a method that parameterizes the detector response to a point source and generates the system matrix on the fly during MLEM or OSEM on graphics hardware. The calibration method, interpolation of coefficient data, and reconstruction results are presented in the context of a recently commissioned small-animal SPECT imager, called FastSPECT III.